Considerations about "defective law". - Casini, Carlo (Medicina e Morale, 2003)
This article wants to be a contribution to trying the most possible correct application of the thought of John Paul II in the encyclical Evangelium Vitae (no. 73) to the issue of the human artificial fertilisation with specific reference to the Italian situation. Analysis is articulated on three levels: juridical, political, educational-cultural. As far as it concerns the level of the juridical science, the author, - after having clarified that legislative gap doesn't mean normative gap - shows what are the norms of the Italian juridical rules that regulate the new subject of the artificial fertilisation. This picture is finalised to understand the degree of juridical improvement and worsening introduced by an "ad hoc" law, comparing in this way the laws in force with the reform approved from the Italian Parliament in June 18th, 2002. The investigation in the political field moves from the intent to appraise the behaviour of the Catholic parliamentary that wants to modify with a law an existing unfair situation. For this purpose, the steps of the legislative procedure are gone over again and political conditions that make progress them are considered. The educational-cultural aspects concern the demand to do clarity in order to the values at stake as a whole. The support to a defective law that improves an existing situation - and however it is expression of maximum attainable possible good in a particular historical time - must join up with a work of consciences enlightenment. This is a pastoral commitment of the Catholic Church above all, but also of the Catholic parliamentary whose position "must be clear and to everybody well-known". For this reason, the author concludes, the educational strategy must not feel extraneous to the appointment to get a however defective law, that moves in the direction of the same value that presides to the educational and cultural message. Finally, also explaining the limits, the objectives, the reasons of a defective law is an aspect of remarkable educational and cultural meaning.